Réponses

2013-12-28T23:44:06+01:00
Bonsoir,

(\dfrac{x^2+1}{e^x})'=\dfrac{(x^2+1)'e^x-(x^2+1)(e^x)'}{(e^x)^2}\\\\(\dfrac{x^2+1}{e^x})'=\dfrac{2xe^x-(x^2+1)e^x}{(e^x)^2}\\\\(\dfrac{x^2+1}{e^x})'=\dfrac{[2x-(x^2+1)]e^x}{(e^x)^2}\\\\(\dfrac{x^2+1}{e^x})'=\dfrac{2x-(x^2+1)}{e^x}\\\\(\dfrac{x^2+1}{e^x})'=\dfrac{2x-x^2-1}{e^x}\\\\(\dfrac{x^2+1}{e^x})'=\dfrac{-(x^2-2x+1)}{e^x}\\\\(\dfrac{x^2+1}{e^x})'=\dfrac{-(x-1)^2}{e^x}
il faut que je fasse un tableau de valeur sur [ - 4 ; 1 ]
f(-4) ≈ 928,2
f(-3) ≈ 200,1
f(-2) ≈ 37
f(-1) ≈ 5,4
f(0) = 1
f(1) ≈ 0,7

f est décroissante sur [-4 ; 1] car f ' (x) ≤ 0 sur [-4 ; 1]
merci :)